# For n 1 y x a so there is no point of inection 35

This preview shows page 1. Sign up to view the full content.

This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: →0 x x→0 x→+∞ x→+∞ ln cos(2/x) (−2/x2 )(− tan(2/x)) − tan(2/x) = lim = lim 2 x→+∞ x→+∞ x→+∞ 1/x −2/x3 1/x 2 x→+∞ lim x→0 (2/x2 ) sec2 (2/x) = −2, lim y = e−2 x→+∞ −1/x2 1 1 − sin x x lim x→0 b ln(1 + a/x) ab = lim = ab, lim y = eab x→+∞ 1 + a/x x→+∞ 1/x ln(2 − x) 2 sin2 (πx/2) = lim = 2/π , lim y = e2/π x→1 cot(πx/2) x→1 x→1 π (2 − x) x→1 = limx→+∞ 31. x→0 3 ln(1 + 2x) 6 = lim − = −6, lim y = e−6 x→0 x→0 x 1 + 2x = lim x→0 x − sin x 1 − cos x sin x = lim = lim =0 x→0 x cos x + sin x x→0 2 cos x − x sin x x sin x 1 − cos 3x 3 sin 3x 9 9 = lim cos 3x = = lim x→0 x→0 2 x2 2x 2 33. (x2 + x) − x2 x lim √ = lim √ = lim 2+x+x 2+x+x x→+∞ x→+∞ x→+∞ x x 34. ex − 1 − x ex − 1 ex = lim x = lim x = 1/2 x−x x−1 x→0 xe x→0 xe + e x→0 xe + 2ex 35. lim [x − ln(x2 + 1)] = lim [ln ex − ln(x2 + 1)] = lim ln x→+∞ lim x→+∞ 38. (a) x→+∞ x x→+∞ ex , x2 + 1 x x 1 = lim ln = ln(1) = 0 1 + x x→+∞ 1/x + 1 ln x 1/x 1 = lim = lim =0 n x→+∞ nxn−1 x→+∞ nxn x xn nxn−1 = lim = lim nxn = +∞ lim x→+∞ ln x x→+∞ 1/x x→+∞ lim x→+∞ 0 3x2 − 2x + 1 because it is not a form x→1 3x2 − 2x 0 (a) L’Hˆpital’s Rule does not apply to the problem lim o (b) 40. = 1/2 e e e = lim = lim = +∞ so lim [x − ln(x2 + 1)] = +∞ x→+∞ x2 + 1 x→+∞ 2x x→+∞ 2 lim ln x→+∞ (b) 39. 1 + 1/x + 1 lim x 36. 1 3x2 − 2x + 1 =2 x→1 3x2 − 2x lim 4x3 − 12x2 + 12x − 4 12x2 − 24x + 12 24x − 24 = lim = lim =0 x→1 4x3 − 9x2 + 6x − 1 x→1 12x2 − 18x + 6 x→1 24x − 18 lim Exercise Set 4.7 41. lim x→+∞ 132 1/(x ln x) 2 √ = lim √ =0 x→+∞ 1/(2 x) x ln x 0.15 100 10000 0 42. y = xx , lim+ ln y = lim+ x→0 x→0 ln x = lim −x = 0, lim+ y = 1 x→0 1/x x→0+ 1 0 0.5 0 43. y = (sin x)3/ ln x , lim+ ln y = lim+ lim y = e3 x→0 x→0 x 3 ln sin x = lim+ (3 cos x) = 3, x→0 ln x sin x 25 x→0+ 0 0.5 19 44. lim − x→π/2 4 sec2 x 4 = lim =4 sec x tan x x→π/2− sin x 4 0.5 p/ 2 0 45. e−x ln x − 1 ; e−x e−x ln x 1/x = lim = 0 by L’Hˆpital’s Rule, so o lim e−x ln x = lim x→+∞ x→+∞ ex x→+∞ ex −x e ln x − 1 lim [ln x − ex ] = lim = −∞ x→+∞ x→+∞ e−x ln x − ex = ln x − 1 = 0 0 3 -16 46. lim [ln ex − ln(1 + 2ex )] = lim ln x→+∞ x→+∞ 1 1 = ln ; = lim ln −x x→+∞ e +2 2 horizontal asymptote y = − ln 2 ex 1 + 2ex -0.6 0 -1.2 12 133 47. Chapter 4 ln(ln x) 1 = lim = 0; x→+∞ x ln x x lim y = 1, y = 1 is the horizontal asymptote 1.02 y = (ln x)1/x , lim ln y = lim x→+∞ x→+∞ x→+∞ 100 10000 1 48. y= x+1 x+2 x 1 , ln lim ln y = lim x→+∞ x→+∞ −1 lim y = e x+1 −x2 x + 2 = lim = −1; x→+∞ (x + 1)(x + 2) 1/x is the horizontal asymptote x→+∞ 0 50 0 (b) +∞ 49. (a) 0 (c) 50. (a) y = x 1+ln x ; lim+ ln y = lim+ (b) (c) y = (x + 1) (d) −∞ x→0 ln a x x→0 (f ) −∞ (ln a) ln x (ln a)/x = lim+ = lim+ ln a = ln a, lim+ y = eln a = a x→0 x→0 x→0 1 + ln x 1/x , lim ln y = lim x→0 (e) +∞ same as part (a) with x → +∞ ln a 0 x→0 (ln a) ln(x + 1) ln a = lim = ln a, lim y = eln a = a x→0 x + 1 x→0 x 51. 1 + 2 cos 2x x + sin 2x sin 2x does not exist, nor is it ±∞; lim = lim 1 + x→+∞ x→+∞ x→+∞ 1 x x 52. 2 2 − cos x 2x − sin x 2 − (sin x)/x does not exist, nor is it ±∞; lim = lim = x→+∞ 3 + cos x x→+∞ 3x + sin x x→+∞ 3 + (sin x)/x 3 53. 54. 55. 56. lim =1 lim x(2 + sin 2x) 2 + sin 2x = lim , which x→+∞ x→+∞ x→+∞ 1 + 1/x x+1 does not exist because sin 2x oscillates between −1 and 1 as x → +∞ lim (2 + x cos 2x + sin 2x) does not exist, nor is it ±∞; lim sin x 11 + cos x + does not exist, nor is it ±∞; x2 2x x(2 + sin x) 2 + sin x = lim =0 lim x→+∞ x→+∞ x + 1/x x2 + 1 lim x→+∞ lim+ R→0 (a) (b) V t −Rt/L Le 1 = Vt L lim (π/2 − x) tan x = lim x→π/2 lim x→π/2 x→π/2 π/2 − x −1 = lim = lim sin2 x = 1 cot x x→π/2 − csc2 x x→π/2 1 − tan x = lim π/2 − x x→π/2 sin x 1 − π/2 − x cos x cos x − (π/2 − x) sin x (π/2 − x) cos x x→π/2 = lim −(π/2 − x) cos x −(π/2 − x) sin x − cos x x→π/2 = lim = lim x→π/2 (π/2 − x) sin x + cos x =0 −(π/2 − x) cos x + 2 sin x Supplementary Exercises 4 (c) 134 1/(π/2 − 1.57) ≈ 1255.765849, tan 1.57 ≈ 1255.765592; 1/(π/2 − 1.57) − tan 1.57 ≈ 0.000265 (c) kt − 1 (ln k )k t = lim = ln k + x→+∞ t→0 t→0 t 1 √ ln 0.3 = −1.20397, 1024 1024 0.3 − 1 = −1.20327; ln 2 = 0.69315, 1024 (a) No; sin(1/x) oscillates as x → 0. 57. (b) 58. lim x(k 1/x − 1) = lim + (b) √ 1024 2 − 1 = 0.69338 0.05 -0.35 0.35 -0.05 (c) For the limit as x → 0+ use the Squeezing Theorem together with the inequalities −x2 ≤ x2 sin(1/x) ≤ x2 . For x → 0− do the same; thus lim f (x) = 0. x→0 k + cos x = ±∞. Hence k = −1, and by the rule x2 2 √ −1 + cos x − sin...
View Full Document

## This document was uploaded on 02/23/2014 for the course MANAGMENT 2201 at University of Michigan.

Ask a homework question - tutors are online